The Dual Benefit of Plant Essential Oils against Tuta absoluta - Ben Abdallah, Saoussen; Riahi, Chaymaa; Vacas, Sandra; Navarro-Llopis, Vicente; Urbaneja, Alberto; Pérez-Hedo, Mertixell (MDPI, 2023)
Plant essential oils (PEOs) are being studied as a potential alternative to synthetic pesticides in agriculture. PEOs have the potential to control pests both directly, by being toxic or repellent to pests, and indirectly, by activating plant’s defense mechanisms. In this study, the effectiveness of five PEOs (Achillea millefolium, Allium sativum, Rosmarinus officinallis, Tagetes minuta, and Thymus zygis) on controlling Tuta absoluta and their impact on the predator Nesidiocoris tenuis was examined. The study revelead that PEOs from A. millefolium and A. sativum-sprayed plants significantly reduced the number of T. absoluta-infested leaflets and did not affect the establishment and reproduction of N. tenuis. Additionally, the spraying of A. millefolium and A. sativum increased the expression of defense genes in the plants, triggering the release of herbivory-induced plant volatiles (HIPVs), such as C6 green leaf volatiles, monoterpenes, and aldehydes, which can be messengers in tritrophic interactions. The results suggest that PEOs from A. millefolium and A. sativum can provide a dual benefit for controlling arthropod pests, as they can directly exhibit toxicity against these pests while also activating plant defense mechanisms. Overall, this study provides new insights into using PEOs as a sustainable solution for controlling pests and diseases in agriculture, by reducing synthetic pesticides and promoting the use of natural predators.